2015
DOI: 10.2135/cropsci2014.05.0363
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Combining Ability of F1 Hybrid Sweet Sorghum in Thailand

Abstract: Sweet sorghum [Sorghum bicolor (L.) Moench] is a sugar‐based biofuel crop that is well‐suited to tropical environments. Most sweet sorghum cultivars are open‐pollinated, but hybrids could offer yield and seed production advantages. Fifteen hybrids were generated among five female and three male parents. The hybrids, parents, and three inbred checks were evaluated for sugar yield and related traits under two environments in Thailand in 2013: Field Crop Research Station at Khon Kaen University, Khon Kaen, and Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…This fact indicates that in the genetic control of these traits, nonadditive genes are involved, with the possibility of obtaining promising hybrid combinations. When estimating the combining ability, Bunphan et al (2015) pointed out the nonadditive gene action for plant height, total biomass production, juice extraction, total soluble solids, sugar yield, and ethanol production. In a detailed analysis of the manifested heterosis, the traits showed significance for the average heterosis ( Table 3), indicating that there is a divergence in the allelic frequencies in the lines, which results in a favorable situation for breeding (Cruz & Vencovsky, 1989).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact indicates that in the genetic control of these traits, nonadditive genes are involved, with the possibility of obtaining promising hybrid combinations. When estimating the combining ability, Bunphan et al (2015) pointed out the nonadditive gene action for plant height, total biomass production, juice extraction, total soluble solids, sugar yield, and ethanol production. In a detailed analysis of the manifested heterosis, the traits showed significance for the average heterosis ( Table 3), indicating that there is a divergence in the allelic frequencies in the lines, which results in a favorable situation for breeding (Cruz & Vencovsky, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the heterotic effect in autogamous species is less effectively manifested than in allogamous ones; however, there are some examples of success, such as in rice (Pereira et al, 2008) and grain sorghum (Scapim et al, 1998). Studies on sweet sorghum have shown the existence of heterosis for traits directly or indirectly related to the ethanol production, including soluble solids content, green mass production, and juice yield (Pfeiffer et al, 2010;Bunphan et al, 2015;Reddy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of diallel analysis proposed by Griffing (1956) is widely used in the choice of parents since it allows estimation of general combining ability (GCA) and specific combining ability (SCA), previously defined by Sprague and Tatum (1942). Sweet sorghum has been studied in this manner in several countries, with emphasis on characterizing combining ability to produce ethanol (Makanda et al 2009, Indhubala et al 2010, Sandeep et al 2010, Vinaykumar et al 2011, Umakanth et al 2012, Bunphan et al 2015. These studies have encouraged breeding sorghum to obtain hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, potential parental lines with high sugar yields and disease resistance were identified within a collection of sweet sorghum lines from multiple international sources [20]. Male sterile female parents (A-lines) have been tested with high-sugar male parents for heritability of sugar traits [10,95]. A number of sweet sorghum A-lines were crossed with several high-yielding pollen parents in both studies.…”
Section: Sorghumsmentioning
confidence: 99%